EVALUASI PEMBERIAN KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) TERHADAP KEPUASAN PASIEN DI PUSKESMAS TAMAN SIDOARJO - Puspita Raras Anindita; Khurin In Wahyuni; Indah Nur Agustin; Herni Setyawati (STIKES Rumah Sakit Anwar Medika, 2022)
Pharmaceutical Care is A Pharmaceutical Service Pattern which is oriented by patient. One of Clinical Pharmaceutical Service obtained by patient is IEC (Information, Education, and Communication) Services. IEC Services is a service provider to patient when it gives medicine. The quality of IEC Servises can be measured patient satisfaction according ethics code have been applied from rules. This research is Cross-Sectional Description Research. Total sample from this research is 80 (Eighty) using sampling technique as known as Consecutive Sampling Technique. The Collecting Data is implemented on march until may 2020 with questionnaire. This research obtains rate percentage results IEC Services is 19% for less, 48% for enough, and good 33% for IEC Services. The result of percentage patient satisfaction is 11% for low, 71% for middle, and 18% for high. According to Pearson Product Moment Correlation Analyze between IEC Service variable with satisfaction is 0,899. This value is higher from r table for total of respondent 80 just 0,220. This indicates relation between IEC Services with patient satisfaction. The value r positive indicates a relation directly proportional. Often IEC Services is given, higher patient satisfaction. If there is two-way significance value 0,00. This value is smaller than the significance value is 0,05. This is obtained the correlation between IEC Services with patient satisfaction is significantly. The correlation of two variables is a perfect correlation. This is important to increasing counseling with the pharmacist additional in order to the pharmacist have the time for doing counseling with Pharmaceutical Care Standardisation.